PERAN FILSAFAT DALAM ILMU PENGETAHUAN - Maghfirah Insannia; Nunu Burhanuddin (CV. ADIBA AISHA AMIRA, 2023)
Science has developed greatly from time to time. Philosophy exists because humans feel surprised, because that surprise leads to natural phenomena in increasingly complex problems. Philosophy of science is a branch of philosophy that emerged around the end of the 19th century or towards the 20th century. The development of science which reached its peak in the 19th century during the time of August Comte and his successors, who tended to make the measurement of scientific truth at a positivistic level, made science increasingly detached from its basic philosophical assumptions. This is what inspired the birth of the philosophy of science which in turn has a very urgent (important) position in science. The urgency of philosophy of science can be seen from its role as a critical dialogue partner in the development of science. Philosophy is the parent of science, in the increasingly independent development of science, because there are many who do not have answers, philosophy answers them. The research method for this article uses the library study method, namely a series of actions carried out in collecting library data, namely library literature, both articles and books.